Does epimuscular myofascial force transmission occur between the human quadriceps muscles in vivo during passive stretching? - Freitas, Sandro (2022)
This study sought to examine the shear modulus (i.e., an force index) of three quadriceps muscles [i.e., vastus medialis (VM), vastus lateralis (VL), and rectus femoris (RF)] during passive stretching to determine whether epimuscular myofascial force transmission occurs across muscles. Secondly, this study compared the shear modulus between the quadriceps muscles, in both proximal and distal regions. Twelve healthy individuals were assessed during a passive knee flexion maneuver between 0 and 90 of knee flexion with the hip in two positions: flexed (80 ) vs. neutral (0 ). Muscle electrical activity was also assessed during the testing. No differences were observed between the hip testing positions for myoelectric activity (p > 0.43), and for VL and VM shear modulus (p = 0.12–0.98). Similarly, there were no differences between the proximal and distal regions for all muscles (p = 0.42–0.93). RF showed a higher shear modulus with the hip in the neutral position (p = 0.004). With the hip flexed, the VL showed the greatest shear modulus among the tested muscles (p < 0.025); while with the hip in the neutral position, no differences were observed for shear modulus between VL and RF (p = 0.817). These findings suggest that epimuscular myofascial force transmission (at a muscle belly level) does not occur between the quadriceps muscles when passively flexing the knee until 90 . Whether epimuscular myofascial force transmission occurs in the quadriceps muscles bellies with greater muscle stretch (either through knee flexion or hip extension) remains to be examined.